Comparative studies of two araceous lectins by steady state and time-resolved fluorescence and CD spectroscopy - Dharker, Poorva N.; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Khan, Mohammad Islam; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2009)
Transitions in the tryptophan microenvironment and secondary structure of two monocot lectins from Sauromatum guttatum and Arisaema tortuosum under different denaturing conditions were studied by steady state and time resolved fluorescence and CD spectroscopy. The lectins exist as tetramers with a single tryptophan residue estimated per monomer, present in a polar environment. Quenching with ionic quenchers showed predominantly electropositive environment for tryptophan residues. Acrylamide had maximum quenching effect. A decrease in KI quenching due to lectin denaturation indicated redistribution of charges as a result of possible conformational change. The two values for lifetimes of tryptophanyl population (1.2-1.4 and 6.3-6.4 ns) reduced substantially on quenching or denaturation. Similarly, both the lectins showed a drastic loss of secondary structure in 5 M Gdn-HCl or 6 M Urea or at pH 2.0 and below. For the first time araceous lectins, like legume lectins are shown to bind adenine. The presence of a compact structure at alkaline pH 10.0-12.0 was observed in CD spectra.
Keywords: Araceae lectins; Denaturation; fluorescence; Lifetime spectroscopy; Secondary structure